Secukinumab Provides Sustained Improvements in the Signs and Symptoms of Psoriatic Arthritis: Final 5‐year Results from the Phase 3 FUTURE 1 Study. Issue 1 (14th November 2019) - Mease, Philip J.; Kavanaugh, Arthur; Reimold, Andreas; Tahir, Hasan; Rech, Juergen; Hall, Stephen; Geusens, Piet; Pellet, Pascale; Delicha, Eumorphia Maria; Pricop, Luminita; Mpofu, Shephard; ,
Abstract : Objective: To report the 5‐year efficacy and safety of secukinumab in the treatment of patients with psoriatic arthritis (PsA) in the FUTURE 1 study (NCT01392326). Methods: Following the 2‐year core trial, eligible patients receiving subcutaneous secukinumab entered a 3‐year extension phase. Results are presented for key efficacy endpoints for the secukinumab 150‐mg group (n = 236), including patients who escalated from 150 to 300 mg (approved doses) starting at week 156. Safety is reported for all patients (n = 587) who received 1 dose or more of study treatment. Results: Overall, 81.8%% (193 of 236) of patients in the secukinumab 150‐mg group completed 5 years of treatment, of which 36.4% (86 of 236) had dose escalation from 150 to 300 mg. Sustained improvements were achieved with secukinumab across all key efficacy endpoints through 5 years. Overall, 71.0%/51.8%/36.3% of patients achieved American College of Rheumatology (ACR) 20/50/70 responses at 5 years. Efficacy improved in patients requiring dose escalation from 150 to 300 mg and was comparable with those who did not require dose escalation. Exposure‐adjusted incidence rates for selected adverse events per 100 patient‐years for any secukinumab dose were serious infections (1.8), Crohn's disease (0.2), Candida infection (0.9), and major adverse cardiac events (0.5). Conclusion: Secukinumab provided sustained improvements in the signs and symptoms in the major clinical domains of PsA. Efficacy improved for patients requiring dose escalation from 150 to 300 mg during the study. Secukinumab was well tolerated with no new safety signals.